Effective Chronic Disease Interventions in Nursing Homes: A Scoping Review Based on the Knowledge-to-Action Framework. Issue 5 (20th October 2022) - Boscart, Veronique; Davey, Meaghan; Crutchlow, Lauren; Heyer, Michelle; Johnson, Keia; Taucar, Linda Sheiban; Costa, Andrew P.; Heckman, George
ABSTRACT: Objectives : The purpose of this scoping review was two-fold: 1) to identify effective intervention studies addressing chronic disease for seniors living in nursing homes (e.x. chronic heart failure, diabetes, dementia, etc.), and 2) to describe how consistently the studies' reported their stages of the Knowledge-to-Action framework (2006). Methods : This scoping review involved a systematic search of CINAHL, EMBASE, PubMed and Scopus of intervention studies, published in English and French between 1997 and 2018, that focused on the development, implementation and/or evaluation of a chronic disease management guideline or best practice for older adults 65+ residing within a nursing home (NH). Authors abstracted information specific to the seven stages of the Knowledge-to-Action framework (identifying problem, tailoring to local context, barriers and facilitators to intervention delivery, implementation, monitoring, outcome criteria, and sustainability). Results : Six studies met the inclusion criteria. Procedures for monitoring knowledge use and outcome evaluation were thoroughly described. Other stages of the Knowledge-to-Action framework were not consistently reported, including problem identification related to older adults' needs and within the context of NHs, intervention implementation, evaluation, and sustainability. Of the six studies included, only two met all the pre-defined evaluation outcomes. Conclusions : Given the need for chronic disease management in NHs, researchers are encouraged to report on intervention studies using the Knowledge-to-Action framework to optimize the likelihood that interventions will be suitable for the context of their delivery and introduce sustainable change. Clinical implications : To answer what interventions should be introduced to residents in long-term care, research must clearly demonstrate efficacy, provide enough detail for methods to be reproducible in applied contexts, and consider strategies for sustainability and the holistic needs of residents.